Biodiversity as an environmental service in Brazil's Amazonian forests: Risks, value and conservation - Fearnside, Philip Martin (Environmental Conservation, 1999)
The environmental service provided by the great biodiversity of Amazonian forests is one of several factors leading to the conclusion that much greater efforts are warranted to reduce the destruction of these forests. Risks to biodiversity in Amazonian forests include deforestation, logging, fires, fragmentation, depletion of fauna, invasion by exotic species, and climate change. Financial values assigned to biodiversity depend strongly on the purposes of valuation. Utilitarian benefits include the values of presently-marketed and presently-unexploited forest products, and the monetary value of environmental benefits. Non-monetary values of Amazonian forests are also essential components of decision-making on conservation. Measures of 'willingness to pay' and 'willingness to accept' can be useful as indicators of potential financial flows, but should not be confused with the true values of the forests to society. Valuation for the purpose of setting penalties for destruction of biodiversity is an important legal question in Brazil and must take into consideration additional factors. Conservation of biodiversity in Brazil includes creation of various types of protected areas. The status of these areas varies greatly, with practice frequently deviating from official requirements. Creating reserves that include human occupants has a variety of pros and cons. Although the effect of humans is not always benign, much larger areas can be brought under protection regimes if human occupants are included. Additional considerations apply to buffer zones around protected areas. The choice and design of reserves depends on the financial costs and biodiversity benefits of different strategies. In Brazil, rapid creation of lightly-protected 'paper parks' has been a means of keeping ahead of the advance of barriers to establishment of new conservation units, but emphasis must eventually shift to better protection of existing reserves. Indigenous peoples have the best record of maintaining forest, but negotiation with these peoples is essential in order to ensure maintenance of the large areas of forest they inhabit. The benefits of environmental services provided by the forest must accrue to those who maintain these forests. Development of mechanisms to capture the value of these services will be a key factor affecting the longterm prospects of Amazonian forests. However, many effective measures to discourage deforestation could be taken immediately through government action, including levying and collecting taxes that discourage land speculation, changing land tenure establishment procedures so as not to reward deforestation, revoking remaining incentives, restricting road building and improvement, strengthening requirements for environmental impact statements (RIMAs) for proposed development projects, and creating employment alternatives.
Keywords: Biodiversity; Conservation Planning; Nature Conservation; Protected Area; Biodiversity; Cost; Ethnic Group; Fire; Forest; Review